Evaluation of in-season wheat nutrient uptake changes and nitrogen management for grain and dual purpose winter wheat - Gardner, Tyler R. (Kansas State University, 2017)
An effective nutrient management plan is essential for optimum wheat (Triticum aestivum) yields. The objectives of the first study were to: i.) evaluate changes in concentration of nitrogen (N), phosphorus (P), potassium (K), sulfur (S), copper (Cu), manganese (Mn), and zinc (Zn), within separate plant parts, throughout the growing season, ii.) evaluate the uptake pattern and redistribution of each of these nutrients within the plant throughout the season, and iii.) evaluate the impact of micronutrient and S fertilization on concentration and uptake of nutrients and the potential use of fertilization for biofortification. Three locations were established and sampled every 7 to 10 days during the spring. Samples were divided into leaf, stem, head, spike and grain fractions and analyzed for nutrient concentration. Concentration levels tended to decrease throughout the season in non-grain plant fractions and stay relatively constant in the grain. Harvest grain concentration of Zn was significantly higher with micronutrient fertilization at all locations, suggesting the possibility of Zn biofortification through fertilization. S, Cu, and Zn showed nutrient accumulation increases in all plant fractions until the time period around anthesis (Feekes 10.5.1), at which point leaf and stem fractions decreased in total accumulation while nutrients were remobilized to the grain. N, P, K and Mn showed a similar trend although timing of remobilization varied between locations and treatments. The objectives of the second study were to i.) evaluate the interaction of wheat grazing management and soil and fertilizer N requirements with emphasis on dual purpose wheat, ii.) assess the use of NDVI sensors for N management and forage quantity assessment in wheat grazing systems, and iii.) evaluate forage quality and quantity interactions with N management. Three locations were established and fertilized with N application rates of 0, 34, 67, and 101 kg ha⁻¹ in the fall, followed by simulated grazing. Spring topdress applications were made at rates of 0 and 90 kg ha⁻¹, or a sensor based rate. The impact of grazing on grain production varied by location. NDVI readings correlated with biomass at two of three locations and N recommendations using NDVI sensors resulted in significantly lower N rates and similar yield results to high N application rates. Forage dry matter and N concentration increased with higher N rates.
Keywords: Wheat nutrient uptake; Dual purpose